Regnase-1 Prevents Pulmonary Arterial Hypertension Through mRNA Degradation of Interleukin-6 and Platelet-Derived Growth Factor in Alveolar Macrophages. Issue 13 (23rd August 2022) - Yaku, Ai; Inagaki, Tadakatsu; Asano, Ryotaro; Okazawa, Makoto; Mori, Hiroyoshi; Sato, Ayuko; Hia, Fabian; Masaki, Takeshi; Manabe, Yusuke; Ishibashi, Tomohiko; Vandenbon, Alexis; Nakatsuka, Yoshinari; et al.
Abstract : Background: Pulmonary arterial hypertension (PAH) is a type of pulmonary hypertension (PH) characterized by obliterative pulmonary vascular remodeling, resulting in right-sided heart failure. Although the pathogenesis of PAH is not fully understood, inflammatory responses and cytokines have been shown to be associated with PAH, in particular, with connective tissue disease-PAH. In this sense, Regnase-1, an RNase that regulates mRNAs encoding genes related to immune reactions, was investigated in relation to the pathogenesis of PH. Methods: We first examined the expression levels of ZC3H12A (encoding Regnase-1) in peripheral blood mononuclear cells from patients with PH classified under various types of PH, searching for an association between the ZC3H12A expression and clinical features. We then generated mice lacking Regnase-1 in myeloid cells, including alveolar macrophages, and examined right ventricular systolic pressures and histological changes in the lung. We further performed a comprehensive analysis of the transcriptome of alveolar macrophages and pulmonary arteries to identify genes regulated by Regnase-1 in alveolar macrophages. Results: ZC3H12A expression in peripheral blood mononuclear cells was inversely correlated with the prognosis and severity of disease in patients with PH, in particular, in connective tissue disease-PAH. The critical role of Regnase-1 in controlling PAH was also reinforced by the analysis of mice lacking Regnase-1 in alveolar macrophages. These mice spontaneously developed severe PAH, characterized by the elevated right ventricular systolic pressures and irreversible pulmonary vascular remodeling, which recapitulated the pathology of patients with PAH. Transcriptomic analysis of alveolar macrophages and pulmonary arteries of these PAH mice revealed that Il6, Il1b, and Pdgfa/b are potential targets of Regnase-1 in alveolar macrophages in the regulation of PAH. The inhibition of IL-6 (interleukin-6) by an anti–IL-6 receptor antibody or platelet-derived growth factor by imatinib but not IL-1β (interleukin-1β) by anakinra, ameliorated the pathogenesis of PAH. Conclusions: Regnase-1 maintains lung innate immune homeostasis through the control of IL-6 and platelet-derived growth factor in alveolar macrophages, thereby suppressing the development of PAH in mice. Furthermore, the decreased expression of Regnase-1 in various types of PH implies its involvement in PH pathogenesis and may serve as a disease biomarker, and a therapeutic target for PH as well.